Anatomia deizmu - Klemczak, Stefan (Studia religiologica, 2021)
An Anatomy of Deism: This article surveys a seemingly straightforward topic: seventeenth- and eighteenth-century deism. It is approached from a historical and philosophical standpoint, chiefly via the analyses of Wayne Hudson. An in-depth study of Hudson’s work indicates that we are dealing with an unexpected diversity of views, as outlined in works such as The English Deists. His remarks concerning various concepts which pass for deist would seem to spoil the fun of those who would seek to create simple visions of history and of a range of analytical philosophers. These investigations into deism also take a broader perspective, showing it as a characteristically modern rendition of non-religious divinity, expressed by the term "the god of philosophers". The history of the travails of the separation of philosophical concepts of divinity from religious beliefs is important for at least two reasons. For one, it highlights a philosophical tendency to present a structure of reality independent of traditional religious imaginings, and for another it allows us to consider human historically-conditioned expectations and claims through the variety of ways of portraying "the divine".